Exploitation: Theory and empirics - Daniele Girardi; Nicolás Grau; Roberto Veneziani; Naoki Yoshihara (Queen Mary University of London, School of Economics and Finance, 2025)
This paper develops a novel axiomatic analysis of exploitation as the unequal exchange of labour, derives an empirical exploitation index at the individual level, and provides the first estimation of the distribution of exploitation in the US in 1975-2022. We show that, among possible definitions of exploitation, only one satisfies a small set of formally weak and normatively salient axioms. From this definition, we derive an individual-level exploitation intensity index which provides a new measure of well-being and inequality, complementary to existing ones and able to jointly take into account the distributions of income and work time. In US data, exploitation intensity provides additional information compared with standard income inequality measures and predicts important well-being and political outcomes. Inequality in exploitation increased more than income inequality since 1975.
Keywords: D63; D5; 330; Ausbeutung; Lohnstruktur; Einkommensverteilung; Arbeitsmarktdiskriminierung; Theorie; USA